A DESIGN SUPPORT TOOL FOR IMPROVING MAINTENANCE SCHEDULING PROCESS. (May 2020) - Khalid, W.; Soleymani, I.; Sigsgaard, K. V.; Hansen, K. B.; Agergaard, J. K.; Mortensen, N. H.
Abstract: The challenge of user requirements for maintenance scheduling design in large asset-intensive industries suffers from lack of academic and empirical studies. Therefore, using a representative case study, this paper aims to: (1) identify the current practices and complex scheduling requirements; (2) propose a design support tool to optimize the maintenance scheduling process; and (3) report the gained benefits. The results reveal that the proposed tool can decrease the resource requirements, increase the capacity utilization, and reduce the cost while addressing the complex user requirements.